PENGARUH PEMBERIAN EKSTRAK KULIT BATANG JALOH TERHADAP GAMBARAN MIKROSKOPIS GINJAL TIKUS PUTIH (Rattus novergicus) YANG DIINFEKSI (Trypanosoma evansi The Effect of Wilow Bark Ekstract Administration on Microscopic Feature of Male Rats (Rattus novergicus) Kidney Infected with Trypanosoma evansi) - Nurdiniyah Nurdiniyah; Nazaruddin Nazaruddin; Sugito Sugito; M Nur Salim; Yudha Fahrimal; Siti Aisyah (Jurnal Medika Veterinaria, 2015)
The aims of this study was to examine the ability of willow bark extract to prevent kidney tissue damage from T. evansi infection. This study used 25 rats which were randomly divided into 5 treatment groups, each groups consisted of 5 rats. Rats in control group (K0) were not infected with T. evansi and without administration of willow bark extract. Group 1 (P1) was infected with 103/0,3 ml of T. evansi without willow bark extract administration. Group 2, 3, and 4 were infected with 103/0.3 ml T. evansi and received willow bark extract at dose of 30, 45, and 60 mg/kg bw, respectively. Willow bark extract were administered for 3 days consecutively. On day 4, the rats were sacrificed using chloroform and the kidneys were collected for histopathological examination. Data were analyzed descriptively. The results showed that the administration of willow bark extract at doses of 30 and 45 mg/kg bw were able to prevent damage of tubule cells and glomerular renal, while the administration of 60 mg/kg bw resulted in kidney damage, indicated by necrosis in tubular glomerular cells. It could be concluded that willow bark extract at doses of 30 and 45 mg/kg bw were effective to prevent tissue damage in kidneys.Key words: kidneys, willow, Trypanosoma evansi